2018
DOI: 10.1590/1678-4766e2018036
|View full text |Cite
|
Sign up to set email alerts
|

Diet of Hemigrammus marginatus (Characiformes: Characidae) in the Upper Contas River, Diamantina Plateau (Bahia, Brazil)

Abstract: Studies on the composition of fish diet and on how species exploit food resources are especially relevant in tropical freshwater systems, where dietary plasticity is a commonly used strategy. In this study, we analysed the food spectrum and the environmental, seasonal and ontogenetic variations in the diet of a characid species [Hemigrammus marginatus Ellis, 1911 (Characidae)] in the region of the Upper Contas River, in the Diamantina Plateau, Brazil. We verified an omnivorous/invertivorous and opportunistic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…It was found that juveniles feed mainly on microcrustaceans, digested organic material, and autochthonous insects, while adults consume mainly the last two food items mentioned. Similar results for other fish species have also been found (e.g., Dias et al, 2017a;Barreto et al, 2008). These dietary differences result from differences in energy requirements and morphological limitations (Abelha et al, 2001).…”
Section: Discussionsupporting
confidence: 71%
“…It was found that juveniles feed mainly on microcrustaceans, digested organic material, and autochthonous insects, while adults consume mainly the last two food items mentioned. Similar results for other fish species have also been found (e.g., Dias et al, 2017a;Barreto et al, 2008). These dietary differences result from differences in energy requirements and morphological limitations (Abelha et al, 2001).…”
Section: Discussionsupporting
confidence: 71%
“…and were not recorded in our expeditions. Both have opportunistic habits, being omnivores with a preference for insects, microcrustaceans and filamentous algae (Barreto et al, 2018), a factor that may be associated with competition with O. niloticus.…”
Section: Discussionmentioning
confidence: 99%